A missional understanding of the church, its ministry, especially with regards to its Christ centric liturgical reorientation - Muller, BA (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
This article shows the necessary shift in missional thinking from the functional approach in most congregational studies to create purpose and consumer driven congregations to a foundational approach based on the church being an agent of the missio dei. This switch in rethinking the essential, basic missional identity of the church necessitates a rethinking of